Respuesta :

Answer:

the roots of the equation are x=0 and x=[tex]\frac{5}{3}[/tex]

Step-by-step explanation:

we can move all terms to one side: 3[tex]x^{2}[/tex]-5x=0

and we can obtain x(3x-5)=0

so either x=0 or 3x-5=0

First start by setting your equation equal to zero. We can do this by subtracting 5x from both sides of the equation. This is done so that all the terms with x will be on the left side of the equation.

3x^2 - 5x = 5x - 5x
3x^2 - 5x = 0

Now, looking at our equation we ask ourselves what is common between 3x^2 and 5x as they are grouped on one side. We recognize that both terms have at least one x. So now we factor x out.

x(3x - 5) = 0

Then we set both factors equal to 0 and solve for x.

x= 0

3x-5=0
3x = 5
x = 5/3

So the roots of this equation are x=0 and x=5/3
ACCESS MORE